2018
DOI: 10.1021/acs.iecr.7b04696
|View full text |Cite
|
Sign up to set email alerts
|

Simple Monitoring of Fine Chemical Runaway Reactions in Multipurpose Plants: Nitration of 2,4-Dichloro Benzotrifluoride

Abstract: In the fine chemical industry new production processes are often implemented in multipurpose existing plants with minimum adaptation investments. When the new process involves a potential runaway reaction, a full thermodynamic and kinetic characterization of the system should be performed to evaluate whether the reaction can be safely scaled-up in the selected plant. However, a detailed kinetic characterization is often unsuited because of the huge development rate of new products. In this work a potential run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Wang investigated 854 chemical accidents with casualties in China from 2015 to 2019 and found that the nitration accidents caused the most casualties due to the explosion and fire within the hazardous reaction processes. Researchers have undertaken extensive efforts to ensure the safety of nitration production. …”
Section: Introductionmentioning
confidence: 99%
“…Wang investigated 854 chemical accidents with casualties in China from 2015 to 2019 and found that the nitration accidents caused the most casualties due to the explosion and fire within the hazardous reaction processes. Researchers have undertaken extensive efforts to ensure the safety of nitration production. …”
Section: Introductionmentioning
confidence: 99%